1981
DOI: 10.2135/cropsci1981.0011183x002100020016x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Morphological Development of Alfalfa for Studies of Herbage Quality1

Abstract: A more precise and quantitative method of specifying the morphological development of alfalfa (Medicago sativa L.) is needed for communication among scientists working with the crop and for associating alfalfa phenology and forage quality. A 10‐stage numerical system for individual stems (Stages to 9) was defined, and two procedures for calculating the mean stage of a herbage sample were compared on alfalfa samples grown in the spring, summer, or autumn and representing weekly age increments up to 10 weeks fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
244
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(259 citation statements)
references
References 0 publications
3
244
1
9
Order By: Relevance
“…For this work, we present data on ionic and nutrient composition at 84 days after seeding (DAS) (2nd harvest, on 15 September 2011) and at 299 DAS (7th harvest, on 17 April 2012). The second harvest was conducted when the control plants were at the early flowering stage, corresponding to morphological stage 5 [21]. The seventh harvest was conducted when the control plants were at a late vegetative stage (due to the absence of flowering).…”
Section: Plant Growth and Nutrient Compositionmentioning
confidence: 99%
“…For this work, we present data on ionic and nutrient composition at 84 days after seeding (DAS) (2nd harvest, on 15 September 2011) and at 299 DAS (7th harvest, on 17 April 2012). The second harvest was conducted when the control plants were at the early flowering stage, corresponding to morphological stage 5 [21]. The seventh harvest was conducted when the control plants were at a late vegetative stage (due to the absence of flowering).…”
Section: Plant Growth and Nutrient Compositionmentioning
confidence: 99%
“…The plants were rated for maturity using the meanstage-by-count method of Kalu and Pick (1981). The leaves from 15 of the 20 sampled stems were removed and the leaf area was measured with a Li-Cor 3000 leaf-area planimeter.…”
Section: Harvest and Plant Analysismentioning
confidence: 99%
“…Plants grown under the greatest water stress had low est maturity ratings (Fig. 7), Water stress, therefore, de layed plant phenological development, as measured by the Kalu and Pick (1981) The effect of water stress in delaying plant development has been demonstrated in work on tropical grasses (Wilson and Ng, 1975;Wilson, 1983b). More recently, Gomez et al (1985) reported a linear increase in maturity of alfalfa with irri gation treatments that allowed more évapotranspiration .. Kalu and Pick (1981) meanstage-by-count method, and X = soil-water content at irriga tion in % of field capacity.…”
Section: Plant Maturitymentioning
confidence: 99%
See 2 more Smart Citations